Correlation Between Maternal-Neonatal Vitamin D Status and it’s Related to Supplementation in Mongolian Pregnant Women - Tsedendamba, Naranchimeg; Zagd, Gerelmaa; Radnaa, Otgonbayar; Baatar, Nomundari; NEMEKHEE, ODONGUA (International Journal of Innovative Research in Medical Science, 2022)
Background: Vitamin D deficiency and insufficient in pregnancy can lead to fetal deficiency that may affect chronic disease susceptibility childhood and adulthood. The aim of this study is to investigate the correlation between maternal and neonatal Vitamin D levels at birth and to identify other risk factors among pregnant women in Mongolia. Methods: Hospital-based study was conducted on 528 participants which included 264 mothers and 264 neonates. Pre-delivery maternal blood and neonatal cord blood samples were collected after birth. 25(ОН)D concentration was analyzed in relation to neonatal Vitamin D status, maternal and neonatal characteristics, and maternal Vitamin D intake. Results: The majority of Vitamin D levels in both maternal (76.5%) and neonatal cord (90.5%) blood were in the deficiency range. Only 3.8% of mothers and 1.5% of neonates had levels in the sufficient range at the time of delivery. For maternal demographic factors, total income was significantly different between the groups (P=0.000). The maternal outcomes were no significant associations were found between groups, but neonatal outcomes were associated with maternal Vitamin D status. In terms of Vitamin D supplementation, 27% of women were taken during pregnancy. Of the not supplemented women, 80% were Vitamin D deficient. Conclusions: A high proportion of Vitamin D deficiency was found in both mothers and newborns in our study. There is a strong correlation between the amount of Vitamin D in the mother and in the newborn. A mother’s Vitamin D intake is related to Vitamin D levels in the mother’s blood.